A NEED ANALYSIS FOR LOCAL TOUR GUIDES AT JAGALAN TOURISM VILLAGE IN YOGYAKARTA - Hermenegildus Agus Wibowo,; Marita Nurharjanti,; Rosyidah Jayanti Vijaya, (Journal of Innovation Research and Knowledge, 2024)
Since the tour guides are directly interact with the tourists, they should have the ability to complete their daily responsibilities, such as: greetings, welcomes, introductions, and providing information. The objectives of the research are to identify, describe, and analyse the English language requirements for local tour guides at Jagalan Tourism Village in Yogyakarta. A qualitative research approach was employed, utilizing non-probability sampling techniques such as purposive sampling, snowball sampling, and abundant sampling. Data collection tools included non-participation observation checklists, questionnaires, and structured interview questions. Present Situation Analysis (PSA) and Target Situation Analysis (TSA) were used to analyse the data. The PSA showed that most participants had a basic proficiency in general English, sufficient for guiding tourists at Jagalan Tourism Village. However, TSA indicated that ESP was needed by all participants to focus on integrated language skills (speaking, listening, reading, and writing) and improve vocabulary related to local tourist attractions, arts, cultures, and traditions. It is important for the local tour guides in Jagalan Tourism Village to enhance their English language skills to effectively communicate with tourists and provide an enriching experience while guiding for the village's attractions and culture.